Bone deep - Ireland, Sandra (Novelist) (Gallery Books, 2019)
"A twisty and propulsive read, this dark contemporary novel of sibling rivalry, love, betrayal, and the dire consequences of family fallout brilliantly plays on human fears of loneliness and abandonment"--